Conformal hexagonal boron nitride encapsulation of graphene-skinned glass fiber fabric for enhanced electrical stability - Xiaomin Yang; Yuyao Yang; Shuting Cheng; Hao Yuan; Xuzhao Gai; Wenjuan Li; Fushun Liang; Fan Yang; Kangyi Zheng; Longfei Liu; Wenjing Jiang; Qingxu Su; et al. (Nature Communications)
Abstract Encapsulation is crucial for protecting graphene devices, but traditional whole-package encapsulations usually add bulky structures and reduce their flexibility. Hexagonal boron nitride (h-BN) holds potential for graphene encapsulation, but faces challenges in large-area acquisition and conformal coverage due to limitations in exfoliation and transfer techniques. Graphene-skinned glass fiber fabric (GGFF), made via graphene CVD growth on each fiber of a glass fiber fabric, consists of a hierarchical conductive network, but pressure/deformation-induced inter-fiber contact resistance fluctuations destabilize its electrical conduction. Whole-package encapsulation cannot resolve this, as fails to insulate inter-fiber contacts. Herein, thick, high-quality h-BN films are CVD-grown on each fiber in GGFF, achieving conformal encapsulation. This unlocks conductive network in GGFF, stabilizing electrical conduction while preserving structure stability and flexibility. This also improves GGFF’s resistance to doping and oxidation, extending its service life. This encapsulation strategy is broadly applicable to other two-dimensional materials and complex device structures, promoting reliable nanoelectronics in demanding environments.